Legality of Tawarruq in Islamic Finance - Nur Yuhanis Bt Ismon (Institute for Research and Community Empowerment (LPPM TAZKIA), 2012)
Objective – Islamic finance has been established as an alternative to the conventional banking system which is made up component not permitted under Shariah. Tawarruq is one of the Islamic finance products which commonly used in Islamic banks. This research assesses two important areas which include the principle of Tawarruq in Fiqh perspective and the practical aspect of such principle in Islamic banks in Malaysia.Method – The method used for this research is comparative analysis.Result – This research begins to explore the different views of the proponent and opponents toward the legality of Tawarruq in Fiqh . Instead of considering the basic condition of the valid sale, the other aspect has to be pondered by the contemporary scholars to render Tawarruq is valid sale according to Shariah. The legality of Tawarruq has been debate by some scholars. Due to that, there are different resolution and rulings from Islamic countries on legality of of Tawarruq . In the practical aspect, Tawarruq has been used in Malaysia by Bursa Malaysia Suq Al Sila' as a trading platform and it uses Crude Palm Oil (CPO) as the commodity in Tawarruq transaction. While, in the Middle East, it uses London Metal Exchange (LME) in dealing with commodity transaction through Tawarruq principle.Conclusion – Based on the legal argument on the permissibility of Tawarruq , it can be summarized that Tawarruq is permissible but subject to certain condition. Provided that genuine Tawarruq is permissible than organized Tawarruq in Tawarruq transaction.Keywords: Tawarruq, Murabahah